The Factors Associated with Early Complementary Feeding in Infants under Six months of Age in Fajar Mulya Public Health Center of Pringsewu Regency - Mariana, Tina; Meysira, Qhinta; Isnaini, Maulia (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The provision of complementary feeding (MP-ASI) before infants reach six months of age remains common in the community, despite its potential risks, including health problems such as diarrhea, impaired growth and development, and decreased infant immunity. In the working area of Fajar Mulya Public Health Center, the coverage of exclusive breastfeeding is relatively low, while the prevalence of early complementary feeding remains high. This study aimed to identify factors associated with early complementary feeding in infants under six months of age in the working area of Fajar Mulya Public Health Center of Pringsewu Regency. This research employed an analytical design with a cross-sectional approach. The study population consisted of 216 respondents, from which 76 samples were selected using purposive sampling in the working area of Fajar Mulya Public Health Center of Pringsewu Regency on May 7th, 2025. Data were collected using a questionnaire and analyzed using the Spearman test. The results showed a significant relationship between maternal attitude (p = 0.000 < 0.05), occupation (p = 0.000 < 0.05), and husband’s support (p = 0.000 < 0.05) with early complementary feeding in infants under six months of age in the working area of Fajar Mulya Public Health Center of Pringsewu Regency. This study suggests that the public health center should conduct regular health education programs in collaboration with its nutrition team. By providing routine counseling, it is expected that maternal motivation for early complementary feeding can be reduced.